Synthesis and Characterization of Screen Printed Zn0.97Cu0.03O Thick Film for Semiconductor Device Applications. (23rd November 2014) - Zargar, Rayees Ahmad; Khan, Sharief Ud Din; Khan, Mohd Shahid; Arora, Manju; Hafiz, Aurangzeb Khurram
Abstract : The studies on doped ZnO thick films deposited over large surface area are still a very promising area of research and development. We report characteristic properties of thick film of Zn0.97 Cu0.03 O prepared by the economic screen printing technique. The film was characterized by XRD, SEM, diffused reflectance, FTIR, and dark resistivity measurement techniques. The XRD and SEM studies revealed polycrystalline, single phase, porous, and granular surface morphology of this Cu doped ZnO thick films. The direct band gap energy of this film determined by diffuse reflectance technique is 3.18 eV. IR transmission spectrum measured in 4000–600 cm −1 region at ambient temperature confirmed the incorporation of Cu 2+ ions in ZnO lattice. The DC resistivity measurements reveal semiconducting nature of the sample with activation energy of 0.66 eV.